Accretion phenomena in nearby star-forming dwarf galaxies. Issue Volume 11:Issue S321(2015) (21st March 2017) - Annibali, F.; Tosi, M.; Aloisi, A.; Bellazzini, M.; Buzzoni, A.; Cignoni, M.; Ciotti, L.; Cusano, F.; Nipoti, C.; Sacchi, E.; Paris, D.; Romano, D.
Abstract: We present two pilot studies for the search and characterization of accretion events in star-forming dwarf galaxies. Our strategy consists of two complementary approaches: i) the direct search for stellar substructures around dwarf galaxies through deep wide-field imaging, and ii) the characterization of the chemical properties in these systems up to large galacto-centric distances. We show our results for two star-forming dwarf galaxies, the starburst irregular NGC 4449, and the extremely metal-poor dwarf DDO 68.